(untitled) (Dhaka University Journal of Biological Sciences, 2021)
An attempt was undertaken to detect the soil fungi and diversity of Trichoderma spp in the rhizosphere soil of selected vegetable crops. A total of fifteen fungi viz., Alternaria sp., Aspergillus flavus, A. fumigatus, A. niger, A. ochraceus, Aspergillus sp., Colletotrichum sp., Curvularia sp., Fusarium sp., Mucor sp., Penicillium sp., Rhizoctonia solani, Rhizopus sp., Trichoderma sp. and Syncephalastrum sp. were isolated from rhizospheric soil of brinjal, chili, cucumber, cabbage and onion in Naogaon district. Except Syncephalastrum sp., all the above mentioned fungi including Monilia sp., were isolated from rhizospheric soil of brinjal, cabbage, chili and tomato of Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur. A total of eight types of Trichoderma spp belonging to four species viz., Trichoderma harzianum, T. koningii, T. reesei and T. viride were isolated from nine vegetable fields from Naogaon district and BARI. These Trichoderma spp. may be used in the management of soil borne diseases of vegetable crops. Dhaka Univ. J. Biol. Sci. 30(1): 104-114, 2021 (January)